2003
DOI: 10.1094/mpmi.2003.16.4.360
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Botrytis cinerea Pectin Methylesterase Gene Bcpme1 Reduces Virulence on Several Host Plants

Abstract: The pectinolytic enzyme pectin methylesterase (PME) hydrolyses pectin in methanol and polygalacturonic acid. In the expressed sequence tag library of Botrytis cinerea T4, we identified a 1,041 bp Bcpme1 cDNA potentially encoding a 346-amino acid protein of 37 kDa showing 46.8% identity with Aspergillus sp. PMEs. Bcpme1 is a single copy gene and is similarly expressed in glucose and pectin containing media. To evaluate the role of Bcpme1 in Botrytis cinerea virulence, a mutant in Bcpme1 was generated by gene di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(140 citation statements)
references
References 39 publications
(27 reference statements)
3
129
0
3
Order By: Relevance
“…We also identified a putative pectin methyl esterase that could assist host penetration. Demethylation of highly esterified cell wall pectins may be a prerequisite for their degradation by fungal endopolygalacturonases (Lionetti et al, 2007), and a pectin methyl esterase was required for the full virulence of Botrytis cinerea on Arabidopsis (Valette-Collet et al, 2003). Furthermore, our analysis suggested that C. higginsianum secretes a putative lignin peroxidase.…”
Section: Soluble Secreted Proteins With Annotated Functionsmentioning
confidence: 70%
“…We also identified a putative pectin methyl esterase that could assist host penetration. Demethylation of highly esterified cell wall pectins may be a prerequisite for their degradation by fungal endopolygalacturonases (Lionetti et al, 2007), and a pectin methyl esterase was required for the full virulence of Botrytis cinerea on Arabidopsis (Valette-Collet et al, 2003). Furthermore, our analysis suggested that C. higginsianum secretes a putative lignin peroxidase.…”
Section: Soluble Secreted Proteins With Annotated Functionsmentioning
confidence: 70%
“…This was not unexpected because B. cinerea is known to interact with pectin as part of its infection strategy. It secretes various pectin-degrading enzymes early during infection and requires some of these enzymes, including PG1, PG2, and PME1, for full virulence (ten Have et al, 1998;Valette-Collet et al, 2003;Kars et al, 2005b;Espino et al, 2010). Additionally, Arabidopsis plants expressing an antisense construct of the polygalacturonase inhibitor PGIP1 are significantly more susceptible to B. cinerea (Ferrari et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that plant immunity to B. cinerea might be affected by pectin content in the host cell wall because this pathogen requires polygalacturonases and pectin methylesterases for full virulence (ten Have et al, 1998;Valette-Collet et al, 2003;Kars et al, 2005b;Espino et al, 2010). Because B. cinerea is genetically diverse and has a high diversity of polygalacturonases (Rowe and Kliebenstein, 2007), we measured relative fungal growth at both 2 and 3 d postinoculation (dpi) using 10 different B. cinerea isolates ( Figure 6).…”
Section: Gae1 and Gae6 Are Required For Immunity To Specific B Cinermentioning
confidence: 99%
“…Apart from cellulose and hemicellulose, pectin is the main and the most complex polysaccharide of plant cell walls. Pectinolytic enzymes are among the first to be secreted by plant pathogens and include, polygalacturonases, pectate and pectin lyases, as well as pectinesterases (Alghisi and Favaron 1995;Valette-Collet et al 2003). Plants in turn produce enzymes which can inhibit the activity of microbial enzymes.…”
Section: Microsynteny To Rice and Putative Candidate Genes For Rrs2mentioning
confidence: 99%